Reinterpretasi Filosofi Tri Hita Karana Dalam Arsitektur Bambu Bali: Menghubungkan Manusia, Alam dan Dewa - Luqiana, Anita (Universitas Medan Area, 2024)
Penglipuran Village is one of the traditional villages of Bangli Regency, Bali Province, Indonesia. This village is known as one of the cleanest villages in the world. This village is also one of the traditional villages and also a tourist village in Bali. However, despite its popularity, Bali still maintains its local cultures to this day. Local culture in Bali can be seen from traditional buildings. One of them is Tri Hita Karana, Tri Hita Karana is a philosophy that must be considered by architects who will design buildings in Bali. The Tri Hita Karana philosophy is defined as three causes of prosperity in life. The purpose of this research is to know and understand Tri Hita Karan. And how do people in Bali apply the concept of the Tri Hita Karana philosophy using bamboo materials. This research uses a data collection method which is used by searching for data based on journals or articles as well as viewing and reading archives such as looking at photos and reading books/journals. Tri Hita Karana was implemented in the form of Parahyangan, which is a unique sacred area location such as a temple. Pawongan, means the community in Penglipuran Village and the traditional organizations that exist to improve and maintain harmonious relations between humans and fellow humans. Pabelasan, means that the local community preserves the environment, such as the Bamboo Forest. The use of natural materials such as bamboo is an effort to maintain harmonious relations between humans and nature.